Comparison of Disintegration and Dissolution of Piroxicam Capsule Products Marketed in Thailand - Teerapong, Pramote; Jaetleela, Somboon; 7angkuptanon, Kritsanaporn; Thathiengtham, Chureeporn (Journal of Basic and Applied Pharmacology, 2015)
Piroxicam is a widely used oxicam nonsteroidal antiinflammatory drug (NSAID). There are at least 23 brands of piroxicam capsule oral dosage products marketing in Thailand. The United States Pharmacopeia (USP) XXlI requires the dissolution test for piroxicam capsule products because a drug with very slightly solubility like piroxicam may possess a rate-limiting step for its absorption and have the bioavailability problem. The purpose of this study was to evaluate and compare the disintegration and dissolution of the available piroxicam capsule products using the United States Pharmacopeia dissolution test for piroxicam capsules. Of 9 brands of piroxicam capsules evaluated, 3 brands failed to meet the USP requirement. And of these 3 brands, 2 brands products showed the slowest disintegration. The other 6 brands conformed the USP dissolution standard and displayed better disintegration. The failure of the 3 brands products to meet the USP requirement for dissolution most likely indicates inappropriate or poor formulations that could result in altered bioavailability and should be taken into account by health care providers concerning the standard, equivalency and efficacy of the mutt/source piroxicam products available in the market. This study is also useful for guiding to seek the highly therapeutic efficacy preparations and help to consider which preparations need to be reformulated. However, drugs which have different dissolution performance were not necessarily always or significantly different in therapeutic outcome. So it is needed to further study their bioavailability in man.